GERAKAN BUPOLO MEMBACA SEBAGAI MEDIA PEMBELAJARAN MASYARAKAT DI KABUPATEN BURU - M Chairul Basrun Umanailo; Abdi Wael (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The Buru Reading Movement is an initiation of service from Iqra Buru University which later became one of the Buru District Government programs that has been running since 2017. This program is intended to improve and create the reading habits of the people in Buru Regency. This research is a qualitative study that aims to describe the implementation of the Buru Reading Movement in Buru Regency. The research location is focused on Namlea District by considering the density and heterogeneity of the community. The number of informants who will be interviewed is 40 people taken purposively. The analysis technique used follows the concept given by Miles and Huberman. The results showed that the reading movement received a positive response from the community and village government where an active role was realized with the availability of village libraries, study rooms and learning houses. The availability of traveling cars only serves Namlea Village by prioritizing services in open spaces and public spaces, while for other villages it is still in the form of participation from the village government and the community to provide reading and learning spaces. However, this movement still leaves several obstacles, such as the availability of types of books that are still general in nature, have not been focused based on the target group and there is no assistance in reading and learning houses so that the utilization of these facilities for school-age people is not yet fully productive.